Tanggung Jawab Hukum PT. Grab Indonesia Cabang Medan Dalam Pengangkutan Barang (grab express) Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen (Studi Di Kementerian Agama Provinsi Sumatera Utara) - Melati Prana Rossi (Universitas Islam Sumatera Utara, 2020)
At this time, communication and information encourage people to develop, both socially and non-socially along with the development of technology. Currently, there are transportations that can be booked and paid for online system. One type of transportation that uses this online system is Uber, Go-jek, and Grab. Grab is a Malaysian company, which operates in Indonesia which is engaged in the application of technology marketing in cooperation with the car rental company. Grab is doing deals that offer based on mobile applications. Uber application can be downloaded on service user smartphones. The purpose of this research is to find out and analyze the legal liability to consumers if the goods sent are damaged, and analyze what are the obstacles faced by the consumers to the driver if the goods sent are damaged.. Legal provisions in the liability of PT. Grab Indonesia, it is a company where its activities use application technology as a transaction tool to provide easy access for consumers to order goods and there are any obstacles faced by the consumers against Medan branch Indonesian Grab drivers. PT. Grab Indonesia applies 2 (two) forms of partnership agreement system, namely: a written partnership agreement system that is implemented when a Partner or driver registers for the first time at the branch office of PT. Grab Indonesia and the second, it can be done electronically. Partnership Cooperation Agreement in a written letter between partners or drivers with PT. Grab Indonesia can be known about the rights and obligations between partners / drivers and PT. Grab. Keywords: Liability, PT. Grab Indonesia, Freightage (Grab Express)